Examining the mechanical response and microstructural evolution of heat-treated Al-5Si-3Cu alloy for automotive applications - Ajide O.O.; Adedokun O.C.; Idusuyi N.; Kumar N.; Aogo O.A.; Ajao O.J.; Adebayo A.S.; Sexena K.K.; Joshi A.; Prakash C. (My University, 2025)
Aluminium-Silicon (Al-Si) based alloys are gaining more prominence among researchers for automotive applications. In this paper, the impact of copper alloying element and artificial ageing treatment on the mechanical response and microstructural evolution of Al-Si based alloys synthesised from aluminium scrap are examined, as there is need to gear up the urge for the usage of metallic scraps for production of alloys for automotive applications. The as-cast Al-Si alloy and its form with copper as alloying element (1.5% and 3% Cu) were produced using liquid metallurgy route. Solution heat treatment was carried out at 500℃ and artificial ageing was carried out at 190℃ for 0.5, 1, 1.5, 2 and 2.5 h. Mechanical properties and microstructural characterisations of the as-cast and artificially aged forms of Al-Si based alloys were performed. The hardness tests were performed according to ASTM A29/A29M–15. Impact strength was determined according to ASTM D256. Tensile tests were performed based on ASTM E8. Microstructures of the synthesised Al-Si alloys were examined using optical microscopy and scanning electron microscopy techniques. In as-cast condition of the Al-5Si-Cu alloy, impact strength increases with increase in copper content. Al5Si-Cu alloy with 3% copper content and artificially aged at 190°C for 2.5 h exhibited the highest impact strength. Hardness number increases with the increase in copper content up to 1.5% and the ageing time. Additional increase in the ageing time yielded decrease in the hardness number. Results revealed that artificial ageing enhances mechanical and microstructural characteristics of the Al-Si alloys. Ageing treated Al-Si alloys exhibited peak hardness, impact strength and ultimate tensile strength (UTS) values of 77.47 kgf/mm2, 17 J/mm2 and 137.80 MPa, respectively. The obtained results are indicative of mechanical properties enhancement when compared with as-cast Al-Si alloys with maximum hardness, impact strength and UTS of 43.71 kgf/mm2, 12.92 J/mm2 and 123.18 MPa, respectively. Significant improvement in mechanical properties was achieved in Al-Si-Cu alloy with copper content and artificial ageing when compared to that without copper inclusion. This may be attributed to the evolution of equiaxed precipitates and the fact that copper-rich Al-Si-Cu alloys promotes formation of precipitation strengthening phases of α-AlFeMnSi. This study shows that the mechanical properties of Al-5Si-Cu alloys produced using aluminium scrap-based materials were enhanced using artificial ageing treatment and the benefit can be utilised for automotive applications. © 2023 Informa UK Limited, trading as Taylor & Francis Group.